On the micro-foundations of money: The Capitol Hill Baby-Sitting Co-op - Thorsten Hens; Klaus Reiner Schenk-Hoppe; Bodo Vogt (Hamburg Institute of International Economics (HWWA), 2003)
This paper contributes to the micro-foundation of money in centralized markets with idiosyncratic uncertainty. It shows existence of stationary monetary equilibria and ensures that there is an optimum quantity of money. The rational solution of our model is compared with actual behavior in a laboratory experiment. The experiment gives support to the theoretical approach.
Keywords: E42; C73; E41; E40; C92; C91; 330; micro foundations of money; optimal; quantity of money; Geldtheorie; Mikroökonomische Fundierung; Tauschwirtschaft; Kinderbetreuung; Geldnachfragetheorie; Geldmenge; Theorie; Tauschring